Evaluation and Management of Premalignant Conditions of the Esophagus: A Systematic Survey of International Guidelines. Issue 9 (October 2019) - Ramai, Daryl; Lai, Jonathan K.; Ofori, Emmanuel; Linn, Sandar; Reddy, Madhavi
Abstract : Esophageal cancer represents one of the most lethal forms of malignancy. The growing incidence of esophageal adenocarcinoma represents an emerging public health concern. This review article summarizes current diagnostic, management, and therapeutic practices of premalignant conditions of the esophagus including Barrett's esophagus, tylosis, granular cell tumors, achalasia, and the ingestion of caustic substances. Our report provides clinicians and academics with a global clinical perspective regarding presentation, surveillance guidelines, and therapeutic management of these esophageal conditions.